Seismic Capacity Assessment of Unreinforced Brick Masonry Building Performed According To Eurocode - Gautam, Raul; Paudel, Kshitiz (Technical Journal, 2020)
Brick Masonry Building with cement sand mortar is a common type of building typology in Nepal. Regardless of being one of the eldest construction technology, the behavior of masonry building is still a matter of study. The uncertainty in the behavior of masonry structures is due to material heterogeneity, complex behavior under different loading conditions and may be due to less research in this arena. Different modeling strategies are used and proposed worldwide to design and to identify the seismic performance of Masonry Building. The analysis strategy ranges from the simple linear method, equivalent frame method, static nonlinear method to dynamic nonlinear, which may be chosen according to engineering design aims and research purpose. In this attempt, authors choose two degrees of freedom 3D model of Unreinforced Brick Masonry Structures which catches both overturning and hysteresis mechanisms due to the shear response implemented by the TREMURI program with static nonlinear procedures. This verified method of modeling and analysis is applied to assess the performance of three different Unreinforced Brick Masonry buildings of the same plans with different numbers of storey.